Mandibular brown tumor as the first manifestation of primary hyperparathyroidism: A case report - Muna Alhusban; Zaid H. Baqain (Elsevier, 2011)
Patients with primary hyperparathyroidism (brown tumor) are usually asymptomatic and clinical presentation of the tumor in the jaws is rarely the first sign of the disease. We report a 45-year-old female patient who presented with a mandibular swelling as the first sign of the disease. Keywords: Brown tumor, Giant cell lesion, Parathyroid adenoma, Primary hyperparathyroidism